(untitled) (Journal of the Management Sciences, 2024)
The success of every economy lies in its labour force which is the aftermath of the education and skills they possess. The paper is aimed at identifying planning strategies for integrating technology into business and entrepreneurship education using content analysis of the literature. The concept of technology, technology integration, Business education, entrepreneurship education and the relevance of technology to business and entrepreneurship education were xrayed. In addition, provision of business and entrepreneurial education technology (BEET), and provision of alternative electricity supply were among the strategies enlisted. The paper concluded that business and entrepreneurship education are key and important aspects of education aimed at producing labour force for economic development and advancement of any nation. The paper recommended among others that efforts should be made by critical stakeholders concerning the provision of business and entrepreneurship education technology (BEET), and provision of alternative electricity supply thereby, ensuring adequate integration and implementation of these technological tools in order to produce labour force who can withstand the current trend in technology thereby advancing business and entrepreneurship growth.